Fibrogenesis & tissue repair (BioMed Central, 2008)
" ... an open access, peer-reviewed online journal featuring high-quality studies providing novel insights into the mechanisms, diagnosis and treatment of human diseases characterized by chronic wound healing and fibrogenesis."
Keywords: Fibrosis : Periodicals; Wound healing : Periodicals; Wound Care; Fibrosis; Wound healing; Wound Healing; Pathology